Palliative Gastrectomy and Survival in Patients With Metastatic Gastric Cancer: A Propensity Score–Matched Analysis of a Large Population-Based Study. Issue 5 (22nd May 2019) - Li, Qin; Zou, Jiahua; Jia, Mingfang; Li, Ping; Zhang, Rui; Han, Jianglong; Huang, Kejie; Qiao, Yunfeng; Xu, Tangpeng; Peng, Ruan; Song, Qibin; Fu, Zhenming
Abstract : OBJECTIVES: The role of palliative gastrectomy in the management of metastatic gastric cancer remains inadequately clarified. METHODS: We analyzed patients with metastatic gastric cancer enrolled in the Surveillance, Epidemiology, and End Results registry from January 2004 to December 2012. Propensity score (PS) analysis with 1:1 matching and the nearest neighbor matching method was performed to ensure well-balanced characteristics of the groups of patients who undergone gastrectomy and those without gastrectomy. Data were analyzed by Kaplan-Meier and Cox proportional hazards regression models to evaluate the overall survival and cancer-specific survival rates with corresponding 95% confidence intervals (CIs). RESULTS: In general, receiving any kind of gastrectomy was associated with an improvement in survival in the multivariate analyses (hazard ratio [HR]os = 0.64, 95% CI = 0.59–0.70, HRcss = 0.63, 95% CI = 0.57–0.68) and PS matching (PSM) analyses (HRos = 0.63, 95% CI = 0.56–0.70, HRcss = 0.62, 95% CI = 0.55–0.70). After PSM, palliative gastrectomy was found to be associated with remarkably improved survival for patients with stage M1 with only 1 metastasis but not associated with survival of patients with stage M1 with extensive metastasis (≥2 metastatic sites). DISCUSSION: The results obtained from the Surveillance, Epidemiology, and End Results database suggest that patients with metastatic gastric cancer might benefit from palliative gastrectomy on the basis of chemotherapy. However, a PSM cohort study of this kind still has a strong selection bias and cannot replace a properly conducted randomized controlled trial.